Determinants of the level of performance of coaches among the University Athletic Association of the Philippines (UAAP) member schools in Metro Manila - Mascardo, Elizabeth D. (2005)
To determine the factors of the level of performance of University Athletic Association of the Philippines (UAAP) school coaches in Metro Manila, an instrument developed on the Docheff Coaches Evaluation Instrument (CEI) rating scale was used to gather data. In the description of the coaches' profile. Multiple regression was used to measure the relationship between the performance ratings of the sports coaches and some personal factors. Only coaching experience was found to have a significant relationship with level of performance.
Keywords: Coaches (Athletics) -- Performances; Coaches (Athletics)